Isolation of E. coli in chicken bishop noses using microbiology and molecular methods / Siti Nazrina Camalxaman ... [et al.] - Camalxaman, Siti Nazrina; Ithnin, Faizah; Haron, Norhisham; Rambely, Azlin Sham; Mohamed, Emida (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Escherichia coli is an organism commonly used as a fecal indicator to assess and monitor the quality of food product to prevent gastrointestinal infection in humans. This study was conducted to detect and isolate the presence of E. coli in poultry products using conventional and molecular detection methods. A total of 10 chicken bishop noses were obtained from two supermarkets in Bandar Puncak Alam. Conventional cultural techniques were performed to screen the presence of E. coli. The amplification of the lamB gene from bacterial isolates detected a single band at 309 bp, confirming the presence of E. coli. In total, 6 out 10 chicken bishop noses were positive for E. coli following screening using standard microbiological techniques coupled with PCR. In summary, conventional methods of E. coli detection should be used in conjunction with molecular based tests to provide optimal diagnostics. Additional work is warranted to further characterize the bacterial isolates to determine its clinical significance.